Pengaruh Model Pembelajaran (Discovery Learning) dengan Menggunakan Media PowerPoint Terhadap Hasil Belajar Fisika Siswa di SMAN 1 Tanoh Alas - Munawirsyah Munawirsyah; Jafri Haryadi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Students feel physics is a difficult subject and full of formulas, the amount of subject matter that must be memorized, lack of motivation from within students to learn physics, and the inaccuracy of models, methods, and learning media used by teachers, so that learning activities feel bored and boring. Theaim of the research to determine student learning outcomes using the Discovery Learning model assisted by Powerpoint media. This type of research is quantitative research. From the data analysis, the average score of the experimental class was 10.32 with a classification standard of 2.19 and the average score of the control class was 10.06 with a division standard of 2.08. In the normality test for the experimental class obtained Lcount< Ltable = 0.066 < 0.246 and in the control class Lcalculate< Ltable = 0.056<0.234 then both classes have normal distributed data. In the homogeneity test of the data of both samples obtained Fhityoung ≤ Ftabel = 0.429 < 0.657 then both samples came from samples that Homogeneous. The results of the t test are obtained tcount>t table = 2.021 > 1.684 so that Ha is accepted. Thus, this study shows that there is a significant influence on the discovery learning learning model using PowerPoint media on student learning outcomes at SMAN 1 Tanoh Alas.